The CIA is trying to recruit Chinese spies for the US government. Chinese citizens don't seem interested - Oiwan Lam (Global Voices, 2025)
Although the videos have addressed the political tensions within the CCP, many find the narratives unconvincing, largely because the U.S has lost its moral high ground under president Donald Trump.
China